Clinical and Image Outcomes of the Hill-Sachs Injury Approach by the Remplissage Technique on the Anterior Shoulder Instability - Flávio de Oliveira França; André Couto Godinho; Diego Pedrosa Capitol Carneiro Leal; Mateus Matos Mantovani; Rafael Rodrigues Frazão; Ricardo Ferreira Mariz (Revista Brasileira de Ortopedia, 2019)
Abstract Objective To evaluate the functional outcome of the remplissage technique, the healing of the capsulotenodesis of the infraspinatus tendon in Hill-Sachs lesion, and the degree of fatty infiltration of the infraspinatus muscle and its postoperative strength. Methods Twenty-five patients with recurrent anterior dislocation of the shoulder and Hill-Sachs lesion with a Hardy index > 20% who underwent the remplissage arthroscopic technique were evaluated with a minimum follow-up of 1 year. Patients underwent a clinical evaluation (Carter-Rowe and Walch-Duplay functional scores, measurement of range of motion and strength) and a magnetic resonance imaging (MRI) exam on the operated shoulder. Results Eighty-eight percent and 92% of the patients had good or excellent scores in the functional assessments of the Carter-Rowe andWalch-Duplay scores, respectively. Amean difference of - 1 kg in the strength of the operated limbwas observedwhen compared with the contralateral limb (p < 0.001), as well as amean difference of 10° in external rotation 1 and 2 (p < 0.001), also compared with the contralateral side. All of the patients who underwent an MRI exam presented high-grade filling of the Hill-Sachs lesion by capsulotenodesis, as well as absence of or minimal fatty infiltration in the infraspinatus muscle. Conclusion The remplissage technique had good/excellent functional score results, despite the discrete, albeit statistically significant, loss of strength and of external rotation amplitude. Successful capsulotenodesis healing and filling of the Hill-Sachs defect were demonstrated.